Integration of Renewable Energy Generating Sources with Micro-Grid (International Journal of Innovative Research in Engineering & Management, 2022)
This paper shows the control of  microgrids at isolated sites powered by hybrid wind and  solar energy sources. The machine used for wind energy  conversion is a double fed induction generator (DFIG)  and the battery bank is connected to a common DC bus  from them. Photovoltaic (PV) arrays are used to convert  solar energy. Solar energy is consumed in a cost-effective  manner with a DC-DC boost converter on DFIG's  common DC bus. The voltage and frequency are adjusted  by the indirect vector control of the line-side converter  with drooping characteristics. It changes the frequency  reference based on the energy level of the battery,  slowing the overcharging or discharging of the battery.  This system can be operated without wind power. Control  algorithms for wind and solar systems include maximum  power point tracking (MPPT). This system is designed for  fully automated operation, taking into account all the  actual conditions of the system also has external power  support to charge the battery without additional  requirements. The simulation model of the system is  developed in the MATLAB environment, and the  simulation results are displayed under various conditions.  wind or sun impermeable, unbalanced load is equally  non-linear, low battery charge state. Finally, the prototype  of the system is implemented using a 5kW photovoltaic  array simulator and a 3.7kW wound rotor asynchronous  machine to generate experimental results to validate the  theoretical model and design.
Keywords: DFIG; Vector Control; Wind Energy; Power quality; photovoltaic solar energy; micro-grid; battery energy storage system; renewable energy system